2023
DOI: 10.7717/peerj.15989
|View full text |Cite
|
Sign up to set email alerts
|

A new pseudoscorpion genus (Garypinoidea: Garypinidae) from the Eocene supports extinction and range contraction in the European paleobiota

Nova Stanczak,
Mark S. Harvey,
Danilo Harms
et al.

Abstract: During the Paleogene, the Holarctic experienced drastic climatic oscillations, including periods of extensive glaciation. These changes had a severe impact on both the flora and fauna causing widespread extinction and range shifts with some taxa retreating to refugia in the Mediterranean Basin. Here we provide evidence for this hypothesis using fossils from the pseudoscorpion family Garypinidae Daday, 1889 (Arachnida: Pseudoscorpiones). This family comprises 21 extant genera from all continents except Antarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…With the exception of its slightly larger size and the position of trichobothrium est on the pedipalpal chela, this extinct species appears morphologically identical to its extant relatives, H. minuta and H. chamberlini —an extreme case of morphological stasis over a 99-million-year period. These results also echo previous studies on fossil pseudoscorpions, which have found similar cases of morphological stasis ( Geißler et al, 2022 ; Johnson et al, 2023 ; Stanczak et al, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…With the exception of its slightly larger size and the position of trichobothrium est on the pedipalpal chela, this extinct species appears morphologically identical to its extant relatives, H. minuta and H. chamberlini —an extreme case of morphological stasis over a 99-million-year period. These results also echo previous studies on fossil pseudoscorpions, which have found similar cases of morphological stasis ( Geißler et al, 2022 ; Johnson et al, 2023 ; Stanczak et al, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…Besides the oldest known pseudoscorpion, Dracochela deprehendor Schawaller, Shear & Bonamo, 1991 in the extinct family Dracochelidae Schawaller, Shear & Bonamo, 1991 from Mid-Devonian (~380–374 Ma) deposits in Gilboa, New York ( Schawaller, Shear & Bonamo, 1991 ; Judson, 2012 ), and the oldest known extant family record, Archaeofeaella hendericxi Kolesnikov et al, 2022 in Feaellidae Ellingsen, 1906 from Upper Triassic deposits in Ukraine ( Kolesnikov et al, 2022 ), all other pseudoscorpion fossils are found in Mesozoic or Cenozoic ambers ( Fig. 2 ) ( Cockerell, 1917 , 1920 ; Schawaller, Shear & Bonamo, 1991 ; Judson, 2009 , 2012 , 2017 ; Henderickx & Boone, 2016 ; Harms & Dunlop, 2017 ; Harvey et al, 2018 ; Porta et al, 2020 ; Wriedt et al, 2021 ; Geißler et al, 2022 ; Kolesnikov et al, 2022 ; Schwarze et al, 2022 ; Johnson et al, 2023 ; Stanczak et al, 2023 ; Novák et al, 2024 ; World Pseudoscorpion Catalog (WPC), 2024 ). Among Mesozoic ambers, twelve species have been described including Heurtaultia rossiorum Judson, 2009 in Cheliferidae Risso, 1827 from Lower Cretaceous (~102 Ma) Archingeay-Les Nouillers amber in France; Ajkagarypinus stephani Novák et al, 2024 from Upper Cretaceous, Santonian (~86–83 Ma) Ajkaite amber in Hungary; and 10 species in one extant genus and seven extinct genera in five extant families from Burmese amber: Electrobisium acutum Cockerell, 1917 and Procheiridium judsoni Porta et al, 2020 in Cheiridiidae Hansen, 1894; Amblyolpium burmiticum ( Cockerell, 1920 ) in Garypinidae Daday, 1889; Protofeaella peetersae Henderickx & Boone, 2016 in Feaellidae; Weygoldtiella plausus Harvey et al, 2018 , Prionochthonius burmiticus Wriedt et al, 2021 , Burmeochthonius kachinae Johnson et al, 2023 and Burmeochthonius muelleri Johnson et al, 2023 in Chthoniidae Daday, 1889; and Proalbiorix gracilis Geißler et al, 2022 and Proalbiorix compactus Geißler et al, 2022 in Ideoroncidae Chamberlin, 1930 ( Cockerell, 1917 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations